2018
DOI: 10.3390/s18092775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strapdown Integration Order and Sampling Rate on IMU-Based Attitude Estimation Accuracy

Abstract: This paper deals with the strapdown integration of attitude estimation Kalman filter (KF) based on inertial measurement unit (IMU) signals. In many low-cost wearable IMU applications, a first-order is selected for strapdown integration, which may degrade attitude estimation performance in high-speed angular motions. The purpose of this research is to provide insights into the effect of the strapdown integration order and sampling rate on the attitude estimation accuracy for low-cost IMU applications. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…where is the corrected angular velocity, i.e., , − −1 + . Also, exp(•) in ( 8) is the matrix exponential operator, which was computed by the second-order Taylor series approximation, as suggested by Lee and Choi [22],…”
Section: B Mimu Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where is the corrected angular velocity, i.e., , − −1 + . Also, exp(•) in ( 8) is the matrix exponential operator, which was computed by the second-order Taylor series approximation, as suggested by Lee and Choi [22],…”
Section: B Mimu Modelmentioning
confidence: 99%
“…is the fixed transformation matrix between global coordinate systems of MIMU and MCS and was calculated by (22),…”
Section: B Performance Evaluationmentioning
confidence: 99%
“…In summary, the INS mechanization and Kalman filter algorithm modification can reduce the number of operations. In addition, the data rate has a significant impact on the computation load [45]. Therefore, combining the simplified algorithm with reducing the sampling rate can significantly improve computational efficiency.…”
Section: Analysis Of Computation Loadmentioning
confidence: 99%
“…Furthermore, no studies have investigated the optimal sampling frequency for a strapped-down inertial MOCAP system. However, it has been shown that a lower sampling frequency results in less accurate reconstruction of the motion [114]. The femur and tibia of the cheetah are modelled as a simple rigid body rotating about a fixed point at 2rad/s to find the minimum sampling frequency threshold for a 3-axis gyroscope.…”
Section: Imumentioning
confidence: 99%
“…As can be seen from ( 7.2), the approximation is more accurate with the inclusion of higher order terms. In [114], Lee et al investigated the effect of the integration order and sampling rate on the estimation accuracy. Their experimental results showed that the effect of the integration order was small when the sampling frequency was high.…”
Section: Extended Kalman Filter (Ekf) Designmentioning
confidence: 99%